Low-luminosity Type II supernovae – III. SN 2018hwm, a faint event with an unusually long plateau. Issue 1 (2nd December 2020) - Reguitti, A; Pumo, M L; Mazzali, P A; Pastorello, A; Pignata, G; Elias-Rosa, N; Prentice, S J; Reynolds, T; Benetti, S; Rodrìguez, O; Mattila, S; Kuncarayakti, H
ABSTRACT: In this work, we present photometric and spectroscopic data of the low-luminosity (LL) Type IIP supernova (SN) 2018hwm. The object shows a faint ( Mr = −15 mag) and very long (∼130 d) plateau, followed by a 2.7 mag drop in the r band to the radioactive tail. The first spectrum shows a blue continuum with narrow Balmer lines, while during the plateau the spectra show numerous metal lines, all with strong and narrow P-Cygni profiles. The expansion velocities are low, in the 1000–1400 km s −1 range. The nebular spectrum, dominated by H α in emission, reveals weak emission from [O i ] and [Ca ii ] doublets. The absolute light curve and spectra at different phases are similar to those of LL SNe IIP. We estimate that 0.002 M⊙ of 56 Ni mass were ejected, through hydrodynamical simulations. The best fit of the model to the observed data is found for an extremely low explosion energy of 0.055 foe, a progenitor radius of 215 R ⊙, and a final progenitor mass of 9–10 M⊙ . Finally, we performed a modelling of the nebular spectrum, to establish the amount of oxygen and calcium ejected. We found a low M( 16 O)≈ 0.02 M_, but a high M( 40 Ca) of 0.3 M⊙ . The inferred low explosion energy, the low ejected 56 Ni mass, and the progenitor parameters, along with peculiar features observed in the nebular spectrum, are consistent with both an electron-capture SN explosion of a superasymptotic giant branch star and with a low-energy, Ni-poor iron core-collapse SN from a 10–12 M⊙ red supergiant.